Impact of Implementing Biophilic Design Principle on High-Rise Buildings in Kuala Lumpur, Malaysia on Public Perception. - Manan, Abd Muluk Abd; Artha, Pande Putu Dwi Novigga; Putri, Ni Putu Ratih Pradnyaswari Anasta (MAJ - Malaysia Architectural Journal, 2025)
This study investigates the impact of implementing biophilic design principles in high-rise buildings on public perception in Kuala Lumpur, Malaysia. Biophilic design, which seeks to integrate nature and natural elements into the built environment, has gained significant attention due to its potential benefits for human well-being and environmental sustainability. However, its application and influence on public perception in high-rise buildings remain understudied. To address this research gap, a mixed-methods approach is employed. Firstly, a comprehensive literature review is conducted to explore the theoretical foundations and empirical evidence related to biophilic design and public perception. Subsequently, surveys are administered to a sample of residents, tenants, and visitors of high-rise buildings in Kuala Lumpur. The surveys capture demographic information and include Likert scale questions and open-ended inquiries to assess participants’ perceptions of biophilic design elements, such as access to natural light, green spaces, indoor plants, and views of nature. Additionally, semi- structured interviews are conducted with key stakeholders involved in the design, construction, and management of high-rise buildings in Kuala Lumpur. These interviews aim to gather insights into the decision-making processes and challenges encountered when implementing biophilic design principles. The findings of this study contribute to the understanding of the impact of biophilic design implementation on public perception in high-rise buildings. By examining the perceptions of residents, tenants, visitors, and key stakeholders, the research aims to identify the perceived benefits and challenges associated with biophilic design elements. The study’s results will inform architects, urban planners, and developers about the potential advantages of incorporating biophilic design in high-rise buildings and its influence on public satisfaction, well-being, and sustainability in the context of Kuala Lumpur, Malaysia.